Origin, Fate, and Function of Epicardium-Derived Cells (EPDCs) in Normal and Abnormal Cardiac Development - Heleen Lie-Venema; Nynke M. S. van den Akker; Noortje A. M. Bax; Elizabeth M. Winter; Saskia Maas; Tuija Kekarainen; Rob C. Hoeben; Marco C. deRuiter; Robert E. Poelmann; Adriana C. Gittenberger-de Groot (The Scientific World Journal)
During heart development, cells of the primary and secondary heart field give rise to the myocardial component of the heart. The neural crest and epicardium provide the heart with a considerable amount of nonmyocardial cells that are indispensable for correct heart development. During the past 2 decades, the importance of epicardium-derived cells (EPDCs) in heart formation became increasingly clear. The epicardium is embryologically formed by the outgrowth of proepicardial cells over the naked heart tube. Following epithelial-mesenchymal transformation, EPDCs form the subepicardial mesenchyme and subsequently migrate into the myocardium, and differentiate into smooth muscle cells and fibroblasts. They contribute to the media of the coronary arteries, to the atrioventricular valves, and the fibrous heart skeleton. Furthermore, they are important for the myocardial architecture of the ventricular walls and for the induction of Purkinje fiber formation.